The Kra Canal conundrum. (3rd July 2019) - Bhardwaj, Prachi
ABSTRACT: The article briefly delves into the historical inception of the idea of the Kra Canal, an artificial navigational waterway, and also address the importance of the matter in the light of its recent preposition for revival. The proposed canal is envisioned as an alternative transit route bypassing the Malacca Strait Dilemma, in turn, having profound repercussions for both the regional and the world order. This article, therefore, highlights the implicit and explicit geo-political and geo-strategic implication of the Thai Canal. It will examine the implications and grey areas for Thailand, China, and the Indian State. In finality, it proposes that the construction of the Kra Canal could not only destabilise the security of the Thai State itself but also threaten the regional order of the region.